Accurate evaluations of both porosity and tortuosity of anodic films grown on rolled AA 1050 and on rolled or machined AA 2024 T3. (27th December 2018) - Giffard, Kévin; Arurault, Laurent; Blanc, Christine; Di Caprio, Dung
Abstract : The porosity of the anodic films grown on aluminium substrates depends on various operating conditions related to the anodization electrolyte and to the applied electrical parameters, as well as to the substrate itself. In the present study, three different aluminium substrates were studied and anodized: AA 1050 (rolled; thickness = 1 mm), AA 2024 T3 (rolled; 1 mm), and AA 2024 T3 (machined; 3 mm). For each type of anodic film, the porosity, as well as its changes during anodization, was accurately characterized using both field‐emission gun scanning electron microscopy (FEG‐SEM) and a reanodization technique. Moreover, for the first time, the corresponding tortuosity was quantified for all studied substrates. Results for rolled AA 2024 T3 and for machined AA 2024 T3 especially showed significant differences in tortuosity values, contributing towards clarifying, in part, their different wettability characteristics or anticorrosion behaviour, so far not clearly explained.